1987
DOI: 10.1017/s0266467400002078
|View full text |Cite
|
Sign up to set email alerts
|

Site characteristics and the distribution of tree species in Mixed Dipterocarp Forest on Tertiary sediments in central Sarawak, Malaysia

Abstract: Site data from 291 forest inventory plots in Mixed Dipterocarp Forest in centralSarawak were simplified by factor analysis. The distribution of the 33 commonest canopy tree species was related to site factor scores by 't' tests. There appears to be a degree of edaphic influence on the distribution of many species. Fairly constant soil characteristics related to the lithology of the parent material appear to be more important than ephemerally variable properties such as organic matter or exchangeable cations. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
137
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(151 citation statements)
references
References 18 publications
12
137
2
Order By: Relevance
“…The decay model using individuals that occur in two or more plots in this analysis decreased significantly with distance, and the distance decay was similar to that demonstrated by Condit et al (2002) using all individuals of trees from Yasuni (Ecuador) and Manu (Peru), by Duque et al (2009) using all individuals of trees from the Colombian Amazonia and by Tuomisto et al (2003a) using specific taxa (Pteridophytes and Melastomataceae) in western Amazonia. Our results are consistent with a significant role for dispersal limitation, a key process that determines species turnover in space under neutral models (Hubbell, 2001;Condit et al, 2002;Duque et al, 2009). However, the comparisons here also emphasise that very dissimilar forests can also occur nearby, and that floristically General soil classification following Malhi et al (2004), a Quesada et al (2009b), b Pitman et al (2008) similar pairs of plots can be found much further away.…”
Section: Is Regional-and Continental-scale Variation In Floristic Comsupporting
confidence: 68%
See 1 more Smart Citation
“…The decay model using individuals that occur in two or more plots in this analysis decreased significantly with distance, and the distance decay was similar to that demonstrated by Condit et al (2002) using all individuals of trees from Yasuni (Ecuador) and Manu (Peru), by Duque et al (2009) using all individuals of trees from the Colombian Amazonia and by Tuomisto et al (2003a) using specific taxa (Pteridophytes and Melastomataceae) in western Amazonia. Our results are consistent with a significant role for dispersal limitation, a key process that determines species turnover in space under neutral models (Hubbell, 2001;Condit et al, 2002;Duque et al, 2009). However, the comparisons here also emphasise that very dissimilar forests can also occur nearby, and that floristically General soil classification following Malhi et al (2004), a Quesada et al (2009b), b Pitman et al (2008) similar pairs of plots can be found much further away.…”
Section: Is Regional-and Continental-scale Variation In Floristic Comsupporting
confidence: 68%
“…Denslow et al, 1987) and are associated with floristic patterns and habitat preferences in Asian tropical forests (e.g. Baillie et al, 1987;Paoli et al, 2006). However, where concentrations of soil cations are low, the concentrations of aluminium may also be important: low concentrations of Mg and Ca are associated with very high aluminium contents in Amazonian soils (Quesada et al, 2009a).…”
Section: Is Regional-and Continental-scale Variation In Floristic Commentioning
confidence: 99%
“…Unlike cation concentration and soil texture, which seem to be widely important in influencing floristic patterns in tropical forests, the role of soil pH may be limited to certain regions or taxa. Soil pH has been found to have significant relationships with floristics in some tropical forests (Baillie 1987;Hall et al 2004;Jones et al 2006) but is unimportant in others (Paoli et al 2006;Ruokolainen & Tuomisto 1998;Tuomisto et al 2003a), including the Ducke Reserve in central Amazonia (Costa et al 2005). Higher species abundances on soils of low pH might be expected due to the evolutionary origin of Amazonian flora of soils of low pH (Partel 2002).…”
Section: Important Environmental Variables For Species Abundancesmentioning
confidence: 99%
“…The clearest evidence for the effects of habitat and soil factors on species distributions comes from studies conducted at mesoscales (Ϸ1-100 km 2 ) (17, 18) and landscape scales (10 2 to 10 4 km 2 ) (19)(20)(21)(22)(23)(24). At these scales, tropical forest landscapes are a mosaic of edaphic types (25,26), with levels of heterogeneity and spatial segregation that allow the effects of dispersal and habitat factors on species distributions and community structure to be relatively easily quantified.…”
mentioning
confidence: 99%